Attributes of God in Creedal Doctrines - Al Mansoori, Salma Saeed Amer (Journal of Posthumanism, 2025)
This research examines the issue of the attributes of God as treated by the creedal doctrines in Islam, and it seeks to analyze the views of theologians and jurists from the early ages up to later generations. The study is divided into four main sections: the intrinsic attributes that pertain to the essence of God, the conceptual attributes that express divine perfection in His ability, will, and knowledge, the active attributes derived from God’s actions in creation, provision, and mercy, and the reported attributes transmitted through the sacred texts that imply aspects of anthropomorphism without compromising God’s transcendence. The research focuses on analyzing the divergent opinions of theological schools—such as the Ashʿarites, the Muʿtazilites, the Karramiyyah, the Sufis, the Salafis, and the Maturidis—while highlighting the ongoing debate concerning the nature of the divine attributes. Each theologian endeavored to present a conception that preserves God’s transcendence from the attributes of created beings by employing textual evidence from the Qur’an and the Sunnah, as well as rational proofs, leading to differences in interpretation between a literal reading of the texts and interpreting them in a manner befitting God’s greatness. The research also discusses the possibility of reconciling the intrinsic, active, and conceptual attributes without falling into anthropomorphism or corporealism, stressing that emphasizing the oneness of God necessitates rejecting any likeness to the created. The study also highlights the importance of a methodology that reconciles the sacred texts with sound reason in achieving a balanced understanding of religious teachings, calling for an interpretation of the texts that preserves God’s perfection without compromising His essence. In conclusion, the research affirms the necessity of maintaining the unity of the Islamic creed and adhering to moderation in addressing the issue of the divine attributes, thereby ensuring that creedal understanding remains consistent with the Qur’anic and prophetic approach followed by the early generations of Muslims.